Neoplasm - Naveed Shahzad, Hafiz (IntechOpen, 2018)
Neoplasm refers to an abnormal tissue growth that arises as a consequence of rapid cell proliferation and continues to grow abnormally even after terminating the stimuli that had instigated the change. It lacks partial or complete functional coordination with that of the normal tissues. Neoplasms are classified depending on the degree and type of tissues involved. Carcinogenesis is a multistep process where a plethora of endogenous and exogenous factors turns out genetic and epigenetic modifications, which collectively amend some critical cellular pathways controlling the proliferation, apoptosis, and differentiation. The cells having aberrant modifications are transformed into malignant ones of which the clonal expansion results in the development of cancer. This book provides the reader with a comprehensive overview of various cancer types along with their molecular mechanisms of initiation and progression. It also describes the current knowledge about the state-of-the-art measures being employed in cancer diagnosis and therapeutics. Particular attention is paid to make this book equally useful for students, practitioners, and expert scientists.